FAKTOR YANG MEMPENGARUHI MASYARAKAT BELUM OOF 01 OESA KEBONSARI WILAYAH KERJA PUSKESMAS GANTRUNG KABUPATEN MADIUN - Andhyk Pranata; Karno .; Hurip Jayadi (Poltekkes Kemenkes Surabaya, 2014)
The Four components of Public Health that serve as supporting factors are Enviroment, Behavior,Health services, Genetics or Heriditary. Human health as well as public health can be influenced byenvironmental factors. (Hiswari, 2003). There are 75 houses categorized as having poor sanitation locatedin the area os Gantrung clinic, Kebonsari village. The aims of this research included the need to describepeople's working Knowledge, Attitudes, Actions as well as community behavior relating to ODF (OpenOefication Free).This descriptive research relied upon descriptive survey approach. Data gathering was carried outby interviews using questionnaire. The total of population in this research consisted of 75 householdsrepresented by respondents.The result of responden interviews indicated that community behavior regarding ODF can bedescribed as follow, 64% of their working knowledge can be categorized as adequate, 49.3% of theirattitude was categori:zedas adequate, 72% of their actions were categorized as adequate, and 64% ofcommunity behavior were categorized as adequate.It can be concluded that in terms of community knowledge, attitude, action, and behaviorallevels, it was categorized as adequate. Residents of Kebonsarivillage should make some changes on theirbehaviors, this is better than elucidation, and a need was identified to improve working knowledgespecially on diseases, hazzard, and effect from ODF. In this casethe action should be helped by Gantrungclinic and the local government.